Within-day test–retest reliability of an accelerometer-based method for registration of step time symmetry during stair descent after ACL reconstruction and in healthy subjects. - Vervaat, Willemijn; Bogen, Bård; Moe-Nilssen, Rolf (Physiotherapy Theory & Practice, 2022)
Background: Symmetry during stair descent can potentially be used as an early functional measure after anterior cruciate ligament reconstruction (ACLR). We have developed a novel application of a single accelerometer-based inertial motion unit (IMU) to identify foot strikes and calculate step times in an ordinary stairway. Purpose: To examine within-day test–retest reliability and measurement error of step time and step time symmetry measured with a body-fixed IMU during stair descent in subjects early after ACLR and in healthy subjects. Methods: Subjects after ACLR were tested twice 6 weeks (N = 15) and twice 3 months (N = 26) postoperatively. Eighteen healthy subjects were tested twice on one occasion. Subjects descended a flight of stairs at preferred speed. Trunk accelerometry data were collected with an inertial motion unit (IMU). Mean step times (MSTs) and limb symmetry index (LSI) of MSTs were calculated. Clinical trials registration number: NCT01279759. Results: Intraclass Correlation Coefficient (ICC (1,1)) for within test–retest reliability varied from 0.87 to 0.96 for MSTs and from 0.58 to 0.87 for LSIs. The 95% confidence interval (CI) for a true value varied from ± 0.02 seconds (s) to ± 0.05 s for MSTs and from ± 4.6 percentage points (pp) to ± 6.6 pp for LSIs. Conclusion: Mean step times measured with a body-fixed IMU during stair descent and limb symmetry indexes calculated from these mean step times are precise and reliable during early post-operative rehabilitation after ACLR and in healthy subjects.